Using a test automation tool for robotic process automation: An empirical study - Santos, Filipa da Silva (2019)
Robotic Process Automation (RPA) uses software robots that interact with systems through their user interface, reducing costs and improving efficiency in automating processes. Despite being a recent term, it is being progressively adopted in companies, being used in many areas, such as IT, Insurance and Human Resources. Although RPA is relatively inexpensive to implement, the cost of licensing is high. To reduce costs, there are open source tools that might be capable of automating process, despite being used for other purposes, such as Test Automation. Therefore, this research aims to test if it is feasible to use a Test Automation tool to automate business processes and identify advantages and disadvantages of using a Test Automation tool as a RPA tool. To accomplish that, a Case Study (CS) was performed in a real company where the same business process was automated, using both a Test Automation tool and a RPA tool. This research presents the comparison analysis and results of an experiment designed with two approaches: a Test Automation tool vs a RPA tool. The results show that despite there were some challenges of using a Test Automation to automate the selected process than with a RPA tool, using Test Automation tools may be useful for companies with low financial resources that aim to find low cost alternatives to RPA tools to automate processes, taking into account the advantages and disadvantages of using a Test Automation tool as a RPA tool provided in this research.